Effect of Intellectual Capital on Financial Performance of Listed Consumer and Industrial Goods Companies in Nigeria - Yusuf, Nguavese Ruth; Nandak, Godswill Yadok; Obafemi, Olutokunbo Tunde (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2024)
The study examined the effect of intellectual capital on the financial performance of listed consumer and industrial goods firms in Nigeria from 2013 to 2022. The population of the study consisted of thirty-two (32) listed consumer and industrial goods firms on the Nigeria Exchange Group, from which a sample twenty-six (26) firms was chosen using the purposive sampling technique. The study used secondary data that was taken from the companies' financial statements, and it employed a longitudinal panel research design. The results showed that capital employed by the listed consumer and industrial goods firms in Nigeria has a positive and significant effect on the financial performance. However, the study found that human capital has no significant effect on the financial performance of listed consumer and industrial goods firms, while structural capital has a negative but significant effect on the financial performance. The study recommends that listed consumer and industrial goods firms should strategically invest to optimize capital employed as this will improve the financial performance.